Bronchus adenoma - Saad, Eduardo N.; Luciani, Wilfredo A.; Suhl, Arnoldo; Goitía, Hugo; Apestegui, Carlos (Cirugía del Uruguay, 1979)
Description of clínica! and diagnostica! aspects and treatment of bro'nchial adenomas. Case material consists of 5 patients.